Kurangnya Aktivitas Fisik dapat Mengakibatkan Obesitas Sentral - Syahrir Zein Rumatumia; Yuke Andriane, dr., M.Kes. (UNISBA Press, 2023)
Abstract. Obesity is a condition that exceeds a person's relative body weight. Obesity can be caused by a lack of physical activity. Ambon province is one of the provinces that does less physical activity in Indonesia. Maluku is a district that has relatively the most problems with central obesity which has a number above the national rate (24.1%). This study aims to determine the relationship between physical activity using the IPAQ questionnaire with central obesity in adults in Amantelu Village, Sirimau District, Ambon City. This research uses observational analytic method with cross sectional research design. The research sample was the people of Amantelu Village, Sirimau District, Ambon City who met the criteria, a total of 70 respondents who were conducted in March - December 2022 using the accidental sampling method. Data were collected using the IPAQ questionnaire for physical activity and measuring waist circumference for obesity. Data were analyzed using pearson statistical analysis. The results showed that 51% of respondents had moderate physical activity, 46% of respondents had strenuous activity. The results of the description of obesity found that 74% of respondents did not experience central obesity. The results showed that there was a positive correlation (r = 0.280) between physical activity and central obesity in the adult community in Amantelu Village, Sirimau District, Ambon City. The lower a person's activity, the higher the risk level of central obesity. Keywords: Central Obesity, IPAQ, Physical Activity Abstrak. Obesitas adalah suatu kondisi yang melebihi berat badan relatif seseorang. Obesitas dapat disebabkan oleh kurangnya aktivitas fisik. Provinsi Ambon merupakan salah satu provinsi yang kurang melakukan aktivitas fisik di Indonesia. Maluku merupakan kabupaten yang relatif paling banyak mengalami masalah obesitas sentral dengan angka di atas angka nasional (24,1%). Penelitian ini bertujuan untuk mengetahui hubungan aktivitas fisik menggunakan kuesioner IPAQ dengan obesitas sentral pada orang dewasa di Desa Amantelu Kecamatan Sirimau Kota Ambon. Penelitian ini menggunakan metode observasional analitik dengan desain penelitian cross sectional. Sampel penelitian adalah masyarakat Desa Amantelu Kecamatan Sirimau Kota Ambon yang memenuhi kriteria sebanyak 70 responden yang dilakukan pada bulan Maret – Desember 2022 dengan menggunakan metode accidental sampling. Pengumpulan data dilakukan dengan menggunakan kuesioner IPAQ untuk aktivitas fisik dan pengukuran lingkar pinggang untuk obesitas. Data dianalisis dengan menggunakan analisis statistik pearson. Hasil penelitian menunjukkan 51% responden melakukan aktivitas fisik sedang, 46% responden melakukan aktivitas berat. Hasil gambaran obesitas didapatkan 74% responden tidak mengalami obesitas sentral. Hasil penelitian menunjukkan bahwa terdapat korelasi positif (r = 0,280) antara aktivitas fisik dengan obesitas sentral pada masyarakat dewasa di Desa Amantelu Kecamatan Sirimau Kota Ambon. Semakin rendah aktivitas seseorang, semakin tinggi tingkat risiko obesitas sentral. Kata kunci: Aktivitas Fisik, IPAQ, Obesitas Sentral